Periviscerokinin (Cap 2b ; CAPA) receptor silencing in females of Rhipicephalus microplus reduces survival, weight and reproductive output - Juan P. Wulff; Kevin B. Temeyer; Jason P. Tidwell; Kristie G. Schlechte; Kimberly H. Lohmeyer; Patricia V. Pietrantonio (Parasites & Vectors, 2022)
Abstract Background The cattle fever tick, Rhipicephalus (Boophilus) microplus, is a vector of pathogens causative of babesiosis and anaplasmosis, both highly lethal bovine diseases that affect cattle worldwide. In Ecdysozoa, neuropeptides and their G-protein-coupled receptors play a critical integrative role in the regulation of all physiological processes. However, the physiological activity of many neuropeptides is still unknown in ticks. Periviscerokinins (CAP2b/PVKs) are neuropeptides associated with myotropic and diuretic activities in insects. These peptides have been identified only in a few tick species, such as Ixodes ricinus, Ixodes scapularis and R. microplus, and their cognate receptor only characterized for the last two. Methods Expression of the periviscerokinin receptor (Rhimi-CAP 2b R) was investigated throughout the developmental stages of R. microplus and silenced by RNA interference (RNAi) in the females. In a first experiment, three double-stranded (ds) RNAs, named ds680-805, ds956-1109 and ds1102-1200, respectively, were tested in vivo. All three caused phenotypic effects, but only the last one was chosen for subsequent experiments. Resulting RNAi phenotypic variables were compared to those of negative controls, both non-injected and dsRNA beta-lactamase-injected ticks, and to positive controls injected with beta-actin dsRNA. Rhimi-CAP 2b R silencing was verified by quantitative reverse-transcriptase PCR in whole females and dissected tissues. Results Rhimi-CAP 2b R transcript expression was detected throughout all developmental stages. Rhimi-CAP 2b R silencing was associated with increased female mortality, decreased weight of surviving females and of egg masses, a delayed egg incubation period and decreased egg hatching (P < 0.05). Conclusions CAP2b/PVKs appear to be associated with the regulation of female feeding, reproduction and survival. Since the Rhimi-CAP 2b R loss of function was detrimental to females, the discovery of antagonistic molecules of the CAP2b/PVK signaling system should cause similar effects. Our results point to this signaling system as a promising target for tick control. Graphical Abstract